Rida Herbal Bitters Improve Cardiovascular Function in High-fat Diet/Streptozotocin-induced Diabetic Rats - Ajao, Folasade Omobolanle; Balogun, Damilola Ayodeji; Iyedupe, Marcus Olaoy; Olagunju, Ayobami; Oparinde, Esther; Adeniji, Luqman; Abulude, Victor; Olaleye, Funmilayo Elizabeth (Journal of Cardiology and Cardiovascular Medicine, 2024)
Background: Effective medication to manage diabetes mellitus-related organ complications with minimal adverse drug toxicity is still in pursuit by scientists worldwide. This study investigated the cardio-protective of Rida herbal bitter (RHB) in a high-fat diet/streptozotocin (STZ)-induced diabetic rats. Methods: Thirty-two matured male Wistar rats (250 ± 20g) were used. The animals were fed with high-fat diet (HFD) for 6 weeks before diabetes induction. A single dose of (35 mg/kgb.wt) freshly prepared STZ was injected intraperitoneally to induce diabetes. The animals were allocated into four groups, 8rats/group. Group I: control; Group II: HFD/STZ-induced diabetic rats; Groups III & IV: HFD/STZ-induced diabetic rats treated with 0.3 ml RHB & 200 mg/kgb.wt metformin respectively. At the end of the experiment, the animals were sacrificed, blood was sample collected via cardiac puncture and the heart was excised and homogenized. The blood samples and cardiac homogenates tissue were centrifuged to retrieve clear supernatant plasma for biochemical assay. Results: Diabetic rats exhibited significant (p < 0.05) elevated blood glucose, insulin, glycated hemoglobin (HbA1c), cardiac biomarkers, lipid profile, malondialdehyde (MDA), pro-inflammatory cytokines, food, and water intake levels with a reduction in body weight, cardiac antioxidant activity, and total protein. RHB administration significantly (p < 0.05) diminished the blood glucose, insulin, HbA1c, cardiac biomarkers, MDA, pro-inflammatory cytokines, lipid profile, food, and water intake, and improved the body weight cardiac antioxidant activity, and total protein. Conclusion: Rida herbal bitter possesses a cardio-protective effect from this study and could be a better alternative medication for managing diabetes and its related cardiovascular complications.